Christianizing South China Mission, Development, and Identity in Modern Chaoshan (Springer International Publishing, 2018)
Christianity flourishes in areas facing profound dislocations amidst regime change and warfare. This book explains the appeal of Christianity in the Chaozhou-Shantou (Chaoshan) region during a time of transition, from a stage of disintegration in the late imperial era into the cosmopolitan and entrepreneurial area it is today. The authors argue that Christianity played multiple roles in Chaoshan, facilitating mutual accommodations and adaptations among foreign missionaries and native converts. The trajectory of Christianization should be understood as a process of civilizational change that inspired individuals and communities to construct a sacred order capable of empowerment in times of chaos and confusion. .